2006
DOI: 10.1529/biophysj.106.083204
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Role of Receptor Recycling in T Cell Polarization

Abstract: Activation of T cells of the immune system involves recognition of the antigen by the T cell receptor and subsequent internalization and recycling of this receptor. We present a numerical model for this process that accounts for the polarity of the intracellular traffic determined by the polarization of the microtubule-organizing center to the immunological synapse. Unexpectedly, the model explains the observed accumulation of receptors at the immunological synapse mainly as dynamic maintenance of the receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 33 publications
6
37
0
Order By: Relevance
“…S8). The KPL-IFF model may implicitly be capturing TCR surface dynamics because directed movement (47) combined with polarized recycling (48,49) of TCR into the immune synapse may balance with TCR internalization (46) to maintain the relatively constant TCR concentration at the immune synapse assumed by the KPL-IFF model, which is consistent with previous calculations (50). A recent study has shown that changing the pMHC affinity can induce a program that over a timescale of several days changes TCR levels (51).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatsupporting
confidence: 82%
See 1 more Smart Citation
“…S8). The KPL-IFF model may implicitly be capturing TCR surface dynamics because directed movement (47) combined with polarized recycling (48,49) of TCR into the immune synapse may balance with TCR internalization (46) to maintain the relatively constant TCR concentration at the immune synapse assumed by the KPL-IFF model, which is consistent with previous calculations (50). A recent study has shown that changing the pMHC affinity can induce a program that over a timescale of several days changes TCR levels (51).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatsupporting
confidence: 82%
“…Fluorescence measurements were performed with the Odyssey Imaging system (LI-COR). A Hill function was fit to the fluorescence over the initial pMHC concentration (in micrograms per milliliter) to determine the EC 50 for each pMHC using Prism. The pMHC concentrations in the functional assays were modified to reflect differences in the immobilization EC 50 as follows: log[pMHC] corrected = log [pMHC] + (log(EC index 50 ) − log(EC 50 )) where the 9V pMHC ligand served as the index.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical models of recycling explained TCR partitioning between the PM and the intracellular pool [4]. More recently, a model of recycling also addressed the polarized TCR accumulation on the TC-APC interface [5]. However, the interface area in this model was a fixed compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, submembranous flow of the actomyosin cortex contributes to molecular concentration in the IS (10,11). Recent data indicate that polarized exocytosis from a rapid recycling pathway is particularly important for the enrichment of some synapse components, including TCR (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%